Approaches to problems of high fertility in agrarian societies - Milbank Memorial Fund (New York, 1952)
The Round Table on "Approaches to Problems of High Fertility in Agrarian Societies," held in connection with the Fund's Annual Conference in 1951, was a follow-up of two previous round-table discussions on related subjects. At the first of these, in 1947, members of the staff of the United Nations and its specialized agencies discussed the development of plans for various types of assistance programs.p1 (BAt the second, in 1949, the emphasis was upon the demographic consequences of modernization, i.e., the tendency for modernization to result in declines in mortality rates before declines in fertility rates occur, and hence to bring about a period of rapid population growth. At the 1951 session, the subject of the present volume, the discussions were concerned with the cultural context of high fertility in preindustrial societies and with ways and means of approaching this problem.s
Paper presented at the 1951 annual conference of the Milbank Memorial Fund.
Keywords: Fertility